Establishment and Application of a Prognostic Risk Score Model Based on Characteristics of Different Immunophenotypes for Lung Adenocarcinoma - Gao, Hong; Liu, Yanhong; Hu, Yue; Ge, Meiling; Ding, Jie; Ye, Qing (Frontiers in Genetics, 2022)
Objective: Lung adenocarcinoma (LUAD) is a highly heterogeneous tumor. Tumor mutations and the immune microenvironment play important roles in LUAD development and progression. This study was aimed at elucidating the characteristics of patients with different tumor immune microenvironment, screening immune-related genes, establishing an effective model to predict the benefits of immunotherapy and prognoses of patients with LUAD. Materials and Methods: We conducted a bioinformatics analysis on data from The Cancer Genome Atlas and Gene Expression Omnibus (training and test sets, respectively). According to the contents of 24 types of tumor-infiltrating immune cells (TIICs) in tumor samples, patients in the training set were clustered into high (Immunity_H), medium (Immunity_M), and low (Immunity_L) immunophenotype groups. The immunophenotypic differentially expressed genes (IDEGs) were used to develop a prognostic risk score (PRS) model. The model was applied to evaluate immunological and prognostic status of patients in the training and 42 surgery patients with early LUAD. Results: Among immunophenotype groups, Immunity_H patients had the best overall survival (OS) and more TIICs than Immunity_L patients. Immunity_M patients had the worst OS, characterized by most CD8+ T and Treg cells and highest expression of PD-1 and PD-L1. After evaluated by the model, low-risk patients in the training set had higher immunophenoscores (IPSs), more TIICs, better tumor immunogenicity, and lower mutation rates of driver genes. Furthermore, the model was a good indicator of the curative effect for immunotherapy-treated patients. Then, the 42 patients with early LUAD were divided into high- and low-risk groups by the PRS model. The levels of TIICs and IPSs were higher in the low-risk patients than in the high-risk ones. The low-risk patients showed stronger antitumor immunity. In addition, their IPSs and PRSs were correlated with EGFR mutations. The low-risk patients also had better progression-free survival (PFS). Conclusion: The model showed good potential for predicting the prognoses and immunotherapy benefits of LUAD patients and could be a new method for early diagnose.